Erythropoietin does not reduce plasma lactate, H+, and K+ during intense exercise - Nordsborg, N. B.; Robach, P.; Boushel, R.; Calbet, J. A. L.; Lundby, C. (Scandinavian Journal of Medicine & Science in Sports, 2015)
It is investigated if recombinant human erythropoietin (rHuEPO) treatment for 15 weeks (n = 8) reduces extracellular accumulation of metabolic stress markers such as lactate, H+, and K+ during incremental exhaustive exercise. After rHuEPO treatment, normalization of blood volume and composition by hemodilution preceded an additional incremental test. Group averages were calculated for an exercise intensity ~80% of pre-rHuEPO peak power output. After rHuEPO treatment, leg lactate release to the plasma compartment was similar to before (4.3 ± 1.6 vs 3.9 ± 2.5 mmol/min) and remained similar after hemodilution. Venous lactate concentration was higher (P < 0.05) after rHuEPO treatment (7.1 ± 1.6 vs 5.2 ± 2.1 mM). Leg H+ release to the plasma compartment after rHuEPO was similar to before (19.6 ± 5.4 vs 17.6 ± 6.0 mmol/min) and remained similar after hemodilution. Nevertheless, venous pH was lower (P < 0.05) after rHuEPO treatment (7.18 ± 0.04 vs 7.22 ± 0.05). Leg K+ release to the plasma compartment after rHuEPO treatment was similar to before (0.8 ± 0.5 vs 0.7 ± 0.7 mmol/min) and remained similar after hemodilution. Additionally, venous K+ concentrations were similar after vs before rHuEPO (5.3 ± 0.3 vs 5.1 ± 0.4 mM). In conclusion, rHuEPO does not reduce plasma accumulation of lactate, H+, and K+ at work rates corresponding to ~80% of peak power output.